Geochemical characteristics of marine and terrestrial shale gas in China. (September 2016) - Dai, Jinxing; Zou, Caineng; Dong, Dazhong; Ni, Yunyan; Wu, Wei; Gong, Deyu; Wang, Yuman; Huang, Shipeng; Huang, Jinliang; Fang, Chenchen; Liu, Dan
Abstract: Although the annual production of shale gas in China was 13 × 10 8  m 3 in 2014, a systematic study on geochemical and isotopic characteristics of these unconventional gases has not been well addressed. In the present study, almost all shale gas samples available in China, including marine shale gas from the Wufeng-Longmaxi Formation in the Sichuan Basin (O3 w–S1 l) and terrestrial shale gas from Chang 7 Member (T3 y 7 ) in the Ordos Basin, were collected and analyzed for their geochemical and isotopic compositions. The shale gas from the Wufeng-Longmaxi Shale is dry gas with an average methane content of 98.38% and records a highest content of CH4 in the world (99.59%), which is consistent with the very high thermal maturity levels of the gas shales that have equivalent vitrinite reflectance (EqVRo) values between 2.4 and 3.6%. The δ 13 C1 values are correspondingly heavy and record a heaviest δ 13 C1 values (−26.7‰) for the shale gases found in the world as well. The average values of δ 13 C1, δ 13 C2 and δ 13 C3 for the Wufeng-Longmaxi shale gas are −31.3‰,  −35.6‰, and −47.2‰, respectively, displaying a complete carbon isotopic reversal (i.e., δ 13 C1  > δ 13 C2  > δ 13 C3 ). δ 2 HCH4 and δ 2 HC2H6 has an average value of −148‰ and −173‰, respectively, also yielding a hydrogen isotopic reversal (i.e., δ 2 HCH4  > δ 2 HC2H6 ). The Chang 7 shale has an average TOC content of 13.81% with vitrinite reflectance (VRo) values between 0.7 and 1.2%. The Chang 7 shale gas is wet gas with an average methane content of 84.90% and is rich in heavy gaseous hydrocarbons (C2 –C5 ). The respective values of δ 13 C1, δ 13 C2 and δ 13 C3 are −48.7‰,  −36.4‰ and −31.3‰, displaying a positive carbon isotopic distribution pattern (i.e., δ 13 C1  < δ 13 C2  < δ 13 C3 ). The average δ 2 HCH4, δ 2 HC2H6 and δ 2 HC3H8 values are −256‰,  −244‰ and −188‰, respectively, and are characterized by a positive distribution pattern (i.e., δ 2 HCH4  < δ 2 HC2H6  < δ 2 HC3H8 ). The differences in gas wetness and carbon and hydrogen isotopic distribution patterns between the shale gases from the Wufeng-Longmaxi and Chang 7 shale are attributed to variations in thermal maturity levels. CO2 is present in low content in both the Wufeng-Longmaxi and Chang 7 shale gases, mostly less than 1%. δ 13 C values for the CO2 in the Wufeng-Longmaxi Formation are between 8.9 and −9.2‰, indicating an inorganic origin from the cracking of carbonate mineral in the shales under high temperatures. In contrast, δ 13 C values of the CO2 in the Chang 7 shale gas range from −8.2 to −22.7‰, indicating an organic origin from the thermal degradation of organic matter. Helium in both the Wufeng-Longmaxi and Chang 7 shale gases is dominantly of curst origin in terms of their R/Ra ratios that vary from 0.01 to 0.08. Positive carbon isotopic distribution pattern is typical of primitive thermogenic gas. However, it can be converted into complete or partial carbon isotopic reversal patterns due to secondary alteration. The causes that yield carbon isotopic reversal include (1) mixing of gases with the same source but different thermal maturity levels; (2) secondary cracking of oil or wet gas; (3) formation water-involved reactions; (4) gas diffusion; and (5) carbon isotope exchange between alkane gases at high temperature. Among them, carbon isotopic exchange between alkane gases at high temperature is a key factor. Nine plots have been drawn based on the shale gases from China, USA and Canada. Among them, the plot of δ 13 C2 versus wetness demonstrates a "lying-S" shape with two inflection points on the gas wetness axis. The wetness value of 1.4% represents a critical point from pyrolytic gas (primary cracking gas) to cracking gas (secondary cracking gas) and whereas the wetness value of 6% marks the end of oil generation. On the diagram of wetness versus δ 13 C, shale gases with wetness values greater than 1.6% are characterized by positive carbon isotopic distribution pattern, whereas a complete or partial carbon isotopic reversals are observed for shale gases with wetness values less than 1.6%. Highlights: Gas from the marine facies Wufeng-Longmaxi shale in Sichuan is dominated by 98.38% CH4 . Marine facies shale gas is characterized by δ 13 C1 >δ 13 C2 >δ 13 C3 and δ 2 HCH4 >δ 2 HC2H6 . The cause for carbon isotopic reversal is high temperature effect.